2009
DOI: 10.1111/j.1471-4159.2009.06150.x
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of internalization of α‐synuclein into microglia: roles of ganglioside GM1 and lipid raft

Abstract: α‐Synuclein (α‐syn) has been known to be a key player of the pathogenesis of Parkinson’s disease and has recently been detected in extracellular biological fluids and shown to be rapidly secreted from cells. The penetration of α‐syn into cells has also been observed. In this study, we observed that dl‐threo‐1‐phenyl‐2‐decanoylamino‐3‐morpholino‐1‐propanol, a glucosyltransferase inhibitor, and proteinase K inhibited the internalization of extracellular monomeric α‐syn into BV‐2 cells, and the addition of monosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
109
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 72 publications
3
109
0
1
Order By: Relevance
“…(b) Entry of a-syn into the recipient cell. Passive diffusion through the plasma membrane, 11,68 endocytosis, 9,11,12,16 and exosome-mediated transfer of a-syn into a recipient cell 14,54 have been reported. Whether an unknown receptor or lipid rafts are involved in a-syn endocytotic uptake remains to be elucidated.…”
Section: Molecular Mechanisms Involved In Intercellular Transfer Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Entry of a-syn into the recipient cell. Passive diffusion through the plasma membrane, 11,68 endocytosis, 9,11,12,16 and exosome-mediated transfer of a-syn into a recipient cell 14,54 have been reported. Whether an unknown receptor or lipid rafts are involved in a-syn endocytotic uptake remains to be elucidated.…”
Section: Molecular Mechanisms Involved In Intercellular Transfer Of Amentioning
confidence: 99%
“…66 This lipid raftmediated endocytosis has been proposed to mediate internalization of Ab peptide by primary neurons 67 and extracellular a-syn by microglial cells. 68 Whether such a mechanism could also mediate a-syn uptake by neuronal cells remains to be investigated (Figure 2b).…”
Section: Molecular Mechanisms Involved In Intercellular Transfer Of Amentioning
confidence: 99%
“…Other unconventional exocytosis mechanisms have been described for PrP (23) and ␣-synuclein (19). Endocytosis of monomeric A␤ (13, 14, 24 -26) and ␣-synuclein (15,(27)(28)(29) and endocytosis of the fibrillar and oligomeric states of some amyloids have also been reported. For instance, fibrilar A␤ can be cleared from the medium by microglia and astroglia (30 -32), whereas oligomeric A␤ can be taken up by neuroblastoma SH-SY5Y cells (33).…”
mentioning
confidence: 98%
“…In addition to studies of its release and uptake, extracellular α-syn has been reported to have effects on neurotoxicity 15,19,20 and inflammation. 14,18,[21][22][23][24] Recent observations that the transplants grafted into the brain of PD patients displayed Lewy bodies 25,26 were considered to be connected with Braak et al's proposal that Lewy body pathology spreads from one brain area to another according to a stereotypic pattern in specific stages. 27 Consequently, more recent in vitro and in vivo experiments [28][29][30][31][32][33] have shown that α-syn aggregates released from neuronal cells can be transferred to neighboring neurons and form Lewy body-like inclusions, providing a mechanistic basis for the spread of α-syn pathology in PD patients and a hypothesis that a prion-like mechanism may underlie the progression of PD.…”
Section: Proteolytic Clearance As a Therapeutic Approach Against Pd Amentioning
confidence: 99%
“…[15][16][17][18] Although the exact mechanism of α-syn uptake has not been established, 11-amino acid imperfect repeats found in the α-syn sequence have been shown to be critical. 16 α-Syn has been shown to be internalized via GM1 and hitherto unknown protein receptors via a lipid raft-dependent endocytosis mechanism, 18 suggesting that cytosolic α-syn can be released from cells and taken up by other cells. In addition to studies of its release and uptake, extracellular α-syn has been reported to have effects on neurotoxicity 15,19,20 and inflammation.…”
Section: Proteolytic Clearance As a Therapeutic Approach Against Pd Amentioning
confidence: 99%